Bioinformatics-Based Analysis of the lncRNA-miRNA-mRNA Network and TF Regulatory Network to Explore the Regulation Mechanism in Spinal Cord Ischemia/Reperfusion Injury - Wang, Dan; Wang, Limei; Han, Jie; Zhang, Zaili; Fang, Bo; Chen, Fengshou (Frontiers in Genetics, 2021)
Background Spinal cord ischemia/reperfusion injury (SCII) is a catastrophic complication involved with cardiovascular, spine, and thoracic surgeries and can lead to paraplegia. Nevertheless, the molecular mechanism of SCII remain ill-defined. Methods Expression profiling (GSE138966) data were obtained from GEO database. Then, differentially expressed (DE) lncRNAs and DEmRNAs were screened out with p < 0.05, and | fold change| > 1.5. Aberrant miRNAs expression in SCII was obtained from PubMed. Functional enrichment analysis of overlapping DEmRNAs between predicted mRNAs in miRDB database and DEmRNAs obtained from GSE138966 was performed using cluster Profiler R package. The lncRNA-miRNA-mRNA competitive endogenous RNA (ceRNA) network was established in light of ceRNA theory. The key lncRNAs in the ceRNA network were identified by topological analysis. Subsequently, key lncRNAs related ceRNA-pathway network and transcription factors (TFs)-mRNAs network were constructed. Simultaneously, the expression levels of hub genes were measured via qRT-PCR. Results The results in this study indicated that 76 miRNAs, 1373 lncRNAs, and 4813 mRNAs were differentially expressed in SCII. A SCII-related ceRNA network was constructed with 154 ncRNAs, 139 mRNAs, and 51 miRNAs. According topological analysis, six lncRNAs (NONRATT019236.2, NONRATT009530.2, NONRATT026999.2, TCONS_00032391, NONRATT023112.2, and NONRATT021956.2) were selected to establish the ceRNA-pathway network, and then two candidate hub lncRNAs (NONRATT009530.2 and NONRATT026999.2) were identified. Subsequently, two lncRNA-miRNA-mRNA regulatory axes were identified. NONRATT026999.2 and NONRATT009530.2 might involve SCII via miR-20b-5p/Map3k8 axis based on the complex ceRNA network. SP1 and Hnf4a acting as important TFs might regulate Map3k8. Furthermore, qRT-PCR results showed that the NONRATT009530.2, NONRATT026999.2, Map3k8, Hfn4a, and SP1 were significantly upregulated in SCII of rats, while the miR-20b-5p was downregulated. Conclusion Our results offer a new insight to understand the ceRNA regulation mechanism in SCII and identify highlighted lncRNA-miRNA-mRNA axes and two key TFs as potential targets for prevention and treatment of SCII.